Pembelajaran Mengenal Huruf Hijaiyah pada Anak Usia Dini Melalui Penggunaan Media Kartu Huruf di Rai’anatun Nahidh - Widya Firdausi Lasty; Elvita Mamy (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
Teaching preparation is essentially a short-term plan to estimate or project what is being done. Thus, preparation for the implementation of learning in elementary schools is an attempt to predict the actions to be taken in learning activities. This research was conducted to find out: how the preparations were made to introduce hijaiyah letters to students, how to plan to introduce hijaiyah letters, how the steps were used to introduce hijaiyyah letters and how the process of introducing hijaiyyah letters to group A students at RA I'anatun Nahidh Research Methodology, General description of research locations, Research Methods, data sources, data collection procedures, data analysis, data validity checks and research stages. The results showed that: the steps used to introduce the hijaiyyah letters were singing hijaiyah letters, every morning children were taught to read iqra', every day six children were taught letters, every day children demonstrated in front of the class six hijaiyah letters, the teacher used cards, pictures and demonstration methods in front of the class. The process of introducing hijaiyyah letters to students every day shows children pictures of hijaiyah letters from alif to yes, they are read together and then written on the blackboard written in the form of six letters hijaiyah letters, then shown With this card media, the six letters are repeatedly shown to the students one by one while explaining the shape and saying it with their mouth so that the letters fit well, then the students one by one demonstrate how to pronounce the letters. Preparation, planning, steps, this learning process must be owned by the teacher because by doing this the teacher is easy to teach, time effective, so learning is fun Keywords: Learning, introduction, hijaiyah letters and card media